Achachairú (Garcinia humilis) Fruit Trees: Botany and Commercial Cultivation in South Florida - Federico W. Sanchez; Jonathan H. Crane; Haimanote Bayabil; Ali Sarkhosh; Muhammad A. Shahid; Bruce Schaffer (EDIS)
This article provides detailed information on the achachairú’s characteristics, botany, and recommended horticultural practices for commercial growers and county and state Extension faculty in south Florida and is also applicable for homeowners and students interested in growing achachairú. Written by Federico W. Sanchez, Jonathan H. Crane, Haimanote Bayabil, Ali Sarkhosh, Muhammad A. Shahid, and Bruce Schaffer, and published by the UF/IFAS Horticultural Sciences Department, March 2024.